Variation in Functional Independence among Stroke Survivors Having Fatigue and Depression - Umaru Muhammad Badaru; Omoyemi Olubunmi Ogwumike; Ade Fatai Adeniyi; Olajide Olubanji Olowe (Neurology Research International)
Objective. This study evaluated variation in functional independence in activities of daily living (ADL) and instrumental activities of daily living (IADL) among individuals with poststroke fatigue (PSF) and poststroke depression (PSD). Methods. A cross-sectional survey involved 65 consenting poststroke survivors who were purposively recruited from physiotherapy clinics of the University College Hospital, Ibadan, Adeoyo Maternity Teaching Hospital, Ibadan, and Federal Medical Center, Gusau. Participants were assessed for symptoms of PSD with short geriatric depression scale-15, PSF with fatigue severity scale, ADL with Barthel Index and IADL with Nottingham extended ADL scale. Data analysis was done using Chi-square and unpaired t-test with significance level being 0.05. Results. Participants’ age ranged from 58 to 80 years. PSD alone (P=0.002) and both PSF and PSD (P=0.02) were significantly associated with ADL, while PSF alone was not (P=0.233). PSD alone (P=0.001) and both PSF and PSD (P=0.001) significantly negatively affected IADL, while PSF alone had no significant effect (P=0.2). Conclusions. Participants with PSD alone and those with both PSF and PSD had lower functional independence in ADL and IADL.